2012
DOI: 10.1007/s00266-012-9868-3
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Mesh Strut: A Novel Instrument for Firm Elevation of the Reconstructed Auricle

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these evidence-based medicine ratings, please refer to the Table of contents or the online instructions to authors at www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Specifically, dimensions of 12–15 mm in height, 20 mm or more in length and no less than 4–5 mm in thickness are fundamental to attain a symmetric projection. If the residual cartilage from the first stage could not match the minimum requirements, particularly in some children, artificial materials such as porous polyethylene 14 , MEDPOR 15 , EH 16 and titanium mesh strut 17 could be an alternative option.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, dimensions of 12–15 mm in height, 20 mm or more in length and no less than 4–5 mm in thickness are fundamental to attain a symmetric projection. If the residual cartilage from the first stage could not match the minimum requirements, particularly in some children, artificial materials such as porous polyethylene 14 , MEDPOR 15 , EH 16 and titanium mesh strut 17 could be an alternative option.…”
Section: Discussionmentioning
confidence: 99%
“…If the rib cartilage is insufficient for the second-stage surgery, a biological material can be used as a replacement. [ 8 9 10 11 12 13 ] Thus, the harvesting of sufficient rib cartilage is beneficial for cartilage framework carving and shaping in the first-stage; late trimming to make up the deformity is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the remaining costal cartilage block might be insufficient and the fixed cartilage wedge block may be absorbed or slip out, resulting in unsatisfactory ear projection [15,16]. Some authors have recently reported that not only the costal cartilage but also artificial materials such as hydroxyapatite or porous polyethylene or titanium mesh strut could be used for elevation [20][21][22]. However, artificial materials lack safety and reliability, as well as published results of research on long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have recently reported that not only the costal cartilage but also artificial materials such as hydroxyapatite or porous polyethylene or titanium mesh strut could be used for elevation [ 20 21 22 ]. However, artificial materials lack safety and reliability, as well as published results of research on long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%